ANALISIS PREDIKSI PEMILIHAN SISTEM ERP PADA PT GUDANG GARAM TBK BERDASARKAN PROSES RANTAI PASOK YANG DIGUNAKAN - Fiona; Jesslyn Clorina; Cynthia Valentini; Lindawati; Kelvin; Joey; Nadiva Surya Permata; Fendy Cuandra; Immanuel Zai (Transpublika Publisher, 2022)
PT Gudang Garam Tbk is a cigarette manufacturer renowned for its unfiltered cigarettes. The number of product lovers compels management to employ supply chain management to maximize distribution. The Enterprise Resource Planning (ERP) system is utilized by PT Gudang Garam Tbk to enhance the efficiency, accuracy, and speed of its business processes. The objective of this study is to determine why PT Gudang Garam Tbk selected Oracle as its ERP system based on its business processes or supply chain. The documentation study approach is employed to collect data for this study. This study employs a qualitative methodology. This study utilizes both primary and secondary data. As a result of the research and discussion, PT Gudang Garam Tbk develops a supply chain strategy that prioritizes efficiency in order to facilitate production and distribution and reduce distribution costs. In fact, the company chose Oracle because it offers various advantages that other ERP systems lack, including the ability to process massive volumes of data, user control that includes restrictions on other users' access, and a server cluster.